(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Background: Age estimation is an essential component of forensic anthropology and medicolegal investigations, partic ularly in adults where conventional skeletal indicators show variable reliability. The sternum, especially the sternomanu brial and xiphisternal joints, has emerged as a potential parameter for adult age estimation using radiological imaging. However, population-specific data regarding sternal fusion patterns are limited in the Haryanvi population. Aim: To evaluate the fusion status of the sternomanubrial and xiphisternal joints using multidetector computed tomog raphy (MDCT) for adult age estimation in a Haryanvi population. Materials and Methods: This cross-sectional study was conducted on thoracic MDCT scans of 72 individuals (43 males and 29 females) aged 26–90 years. Three-dimensional reconstructed CT images were evaluated for fusion status of the sternomanubrial and xiphisternal joints. Fusion patterns were classified as no fusion, partial fusion, and complete fusion. Participants were grouped into seven age categories. Statistical analysis was performed using SPSS version 20.0, and Pearson’s Chi-square test was applied to assess the association between fusion status, age, and gender. Results: Partial fusion was the most common finding at the sternomanubrial joint (41.7%), while complete fusion pre dominated at the xiphisternal joint (77.8%). No statistically significant association was observed between sternomanu brial joint fusion and age (p = 0.868). Although xiphisternal joint fusion also did not demonstrate statistical significance (p = 0.071), a progressive increase in complete fusion with advancing age was observed. Complete xiphisternal fusion was present in all participants aged ≥81 years. Conclusion: MDCT evaluation of sternal joint fusion provides useful baseline data for forensic age estimation in the Haryanvi population. While sternomanubrial fusion demonstrated considerable variability, xiphisternal fusion showed a progressive age-related trend and may serve as a supplementary indicator for adult age estimation when used alongside other skeletal parameters.